Monetary Policy, Liquidity, and the Risk Profitability Nexus: Evidence From Indonesian State and Private Banks - Dadang Agus Suryanto; Acu Kusnandar (Al-Qalam Institute, 2025)
This study aims to analyze the nexus between liquidity, credit risk, capital adequacy, and profitability in the banking sector under varying macroeconomic conditions. A quantitative approach is employed using panel data with a sequential modeling strategy. In the first stage, the effects of policy interest rates and inflation on liquidity, proxied by the Loan-to-Deposit Ratio (LDR), are examined. The second stage analyzes the influence of LDR and the Capital Adequacy Ratio (CAR) on credit risk, as measured by Non-Performing Loans (NPL), using a fixed-effects model. The third stage evaluates the impact of LDR, CAR, and NPL on profitability, proxied by Return on Assets (ROA), using a random effects model. Dummy variables and interaction terms are included to capture structural differences across bank types, with robust standard errors applied to ensure reliability. The results indicate a significant risk–return trade-off: higher liquidity and stronger capital adequacy contribute to improved profitability, while increased credit risk adversely affects financial performance. The findings imply that effective liquidity and capital management are essential for maintaining financial stability and optimizing bank profitability, particularly during periods of economic uncertainty.